PEMUDA DAN PENDIDIKAN LINGKUNGAN DARI PERSPEKTIF KRISTEN - Alon Mandimpu Nainggolan (TANGKOLEH PUTAI, 2020)
It is a historical fact that the ecological crisis is a reality of life, and at the same time the biggest problem that humans face in this age. The decline in environmental quality has now reached a level that can threaten the survival of humans on earth. The environmental crisis occurs because of the misconceptions about the environment (the concept of human-natural relations), the lack of examples in preserving the environment, the preach that exist today have not touched many real problems about the environment around them, and also human egoism in treating others creation. Real efforts both internationally, regionally and locally to overcome the decline of the environment become a necessity and needs in the present and future. One of the most strategic steps is to equip, empower and mobilize youth through education so that they are actively involved in environmental conservation. Through environmental education for youth that hoped the birth of pioneers in providing information about efforts to improve the quality of the environment (to inform), be a role model in maintaining the environment for the community (to inspire) and become an agent to increase community capacity and potential in empowering the environment positively (to empower) . That is why, should not ignore environmental education for youth. The basic thoughts of researchers are that all Christian traditions have the potential to discover and express concern for the environment.